2023
DOI: 10.1186/s12912-023-01428-0
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between moral courage, moral sensitivity, and ethical decision-making by nurse interns: a cross-sectional study

Abstract: Background Clinical decision-making involves ethical issues that become more and more complex. Nurse interns must be more skilled in making rational and timely decisions when facing ethical dilemmas. The contributing factors and their relationships that challenge ethical decision-making among nurse interns must be fully understood, as this level of knowledge can support the development of strategies and interventions that improve the ethical decision-making ability of nurse interns. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 26 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…In line with the findings of this study, some studies have revealed that nurses have reported a high moral courage [ 9 , 28 ]. However, other studies reported the moral courage of nurses to be moderate and low [ 29 , 30 ]. This difference might be attributed to the participants’ different ethical climate, organizational and cultural contexts, work experience, inappropriate working conditions and work environment, lack of organizational support as well as lack of job motivation [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In line with the findings of this study, some studies have revealed that nurses have reported a high moral courage [ 9 , 28 ]. However, other studies reported the moral courage of nurses to be moderate and low [ 29 , 30 ]. This difference might be attributed to the participants’ different ethical climate, organizational and cultural contexts, work experience, inappropriate working conditions and work environment, lack of organizational support as well as lack of job motivation [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…To provide high‐quality nursing services and ensure the sustainable development of the nursing profession, nurses face many ethical issues; at the same time, they are required to be morally competent in their professional performance (Luo et al., 2023). Moral courage is defined as an individual's ability to persist in doing the right thing based on moral principles in the face of knowing risks, even if the consequences are negative (Dinndorf‐Hogenson, 2015; Rakhshan et al., 2021).…”
Section: Introductionmentioning
confidence: 99%